PENGARUH BEBAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA DAN KINERJA PERAWAT RUMAH SAKIT IBU DAN ANAK ZAINAB PEKANBARU - Afrianti Pipin; Sasmita Jumiati; Marzolina Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the effect of workload and organizational commitment on job satisfaction and nurse performance at the zainab maternal and child hospital pekanbaru. The sample in this study amounted to 135 nurses from the entire population of 206 nurses. The research sample was taken by random sampling. Primary data were collected through interviews and questionnaires as instrument to prove the result of the study. The data analysis method uses quantitative descriptive, to test the hypothesis in this study is to use path analysis (path analysis) with the help of spss version 24 program. The result showed that : 1) workload had a positive and significant effect on job satisfaction at zainab pekanbaru maternal and child hospital, 2) organizational commitment had a positive and significant effect on job satisfaction at zainab pekanbaru maternal and child hospital, 3) workload had an effect on positive and significant effect on the performance of nurses at the zainab pekanbaru maternal and child hospital, 4) organizational commitment has a positive and significant effect on the performance of nurses at the zainab pekanbaru maternal and child, 5) job satisfaction has a positive and significant effect on the performance of nurses at the maternal and child hospital zainab pekanbaru, 6) workload has a positive and significant effect on performance through job satisfaction at zainab pekanbaru maternal and child hospital, 7) organizational commitment has a positive and significant effect on performance through job satisfaction at zainab pekanbaru maternal and child pekanbaru.Keywoards : workload, organitazional commitment, job satisfaction, performance